Non-Typeable Haemophilus influenzae Invasion and Persistence in the Human Respiratory Tract - Clementi, Cara; Murphy, Timothy (Frontiers in Cellular and Infection Microbiology, 2011)
Nontypeable Haemophilus influenzae (NTHI) is an opportunistic bacterial pathogen of the human respiratory tract and is a leading cause of respiratory infections in children and adults. NTHI is considered to be an extracellular pathogen, but has consistently been observed within and between human respiratory epithelial cells and macrophages, in vitro and ex vivo. Until recently, few studies have examined the internalization, trafficking, and fate of NTHI in host cells. It is important to clarify this interaction because of a possible correlation between intracellular NTHI and symptomatic infection, and because NTHI infections frequently persist and recur despite antibiotic therapy and the development of bactericidal antibodies, suggesting a possible intracellular state or reservoir for NTHI. How do NTHI enter host cells? Can NTHI survive intracellularly and, if so, for how long? Strides have been made in the identification of host receptors, signaling, endocytosis, and trafficking pathways involved in the entry and persistence of NTHI in the respiratory tract.